2021
DOI: 10.28991/esj-2021-01260
|View full text |Cite
|
Sign up to set email alerts
|

Explaining an Adoption and Continuance Intention to Use Contactless Payment Technologies: During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has affected the lives of people and services, pushing them toward new technologies that are in step with the development of a “New Normal” way of life. Contactless technologies have been realized as a mechanism to reduce the risks of infection, accelerating the move to touchless behaviors. The purpose of this study is to develop an Integrated Expectation-Confirmation and Health Belief Model (ECHBM) to explain an adoption and continuance intention to use contactless technologies during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
71
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(84 citation statements)
references
References 24 publications
(31 reference statements)
9
71
2
2
Order By: Relevance
“…They noted that a large percentage of the people are aware of the technology and are willing to adopt, accept and use it. Similarly in [47] , an integrated expectation confirmation and health belief model (ECHBM) was developed in Thailand to explain the adoption and continuance intention of people to use contactless digital technologies in COVID-19 crises. The authors identified that perceived susceptibility, perceived usefulness, satisfaction and perceived seriousness had a significant impact on the intention to use contactless payment systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They noted that a large percentage of the people are aware of the technology and are willing to adopt, accept and use it. Similarly in [47] , an integrated expectation confirmation and health belief model (ECHBM) was developed in Thailand to explain the adoption and continuance intention of people to use contactless digital technologies in COVID-19 crises. The authors identified that perceived susceptibility, perceived usefulness, satisfaction and perceived seriousness had a significant impact on the intention to use contactless payment systems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature review shows that the 'risk' factor has recently started to be analyzed in terms of health rather than finance [49]. The fear of contagion-according to latest studiesplay a prominent role in the decision to abandon cash for transactional purposes [50] and was a catalyst for contactless payment technology usage [51]. Recent studies also show that the outbreak of COVID-19 played a key role in changing the acceptance and development of branchless banking [52].…”
Section: Literature Review-payment Behavior During the Covid-19 Pandemicmentioning
confidence: 99%
“…For Other innovations that are most pertinent to consumers during the COVID-19 pandemic include contactless payment systems, also known as 'tap-and-go' in some countries. These are cashless payment methods using credit/debit cards or payment-enabled devices such as smartphones (Puriwat & Tripopsakul, 2021). COVID-19 has been a massive catalyst in the shift to a cashless and online shopping society.…”
Section: Gaps and Opportunities Research Directionsmentioning
confidence: 99%